Stabilisasi Tanah Plastisitas Tinggi Menggunakan Semen Dan Difa Soil Stabilizer - Ronny Tigor Sitanggang; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
High plasticity is poor physical and mechanical properties of the soil, so it is deemed not to meet a certain technical properties for bearing a construction. It is usually has a low bearing capacity, high compressibility and high swelling and shrinkage behaviour, where it needs to be stabilized. This study attempted to stabilize high plasticity soils using cement and Difa Soil Stabilizer as addictive material. This study investigated effect of Difa Soil Stabilizer to physical and mechanical properties (UCS test). Difa Soil Stabilizer and cement varied from 0.6%, 0.8%, 1.0%, and 3% and 5% of soil dry weight respectively. UCS test was conducted at optimum water content after 0, 7, and 14 days curing. The results show that Difa Soil Stabilizer could not work optimally without cement. Curing days for soil, cement and Difa Soil Stabilizer increase UCS value. Maximum UCS value (878.7 kPa) was obtained at 14 days of curing for mixture of soil + 5% cement. UCS value for mixture of soil + 3% cement has a lower UCS value (344.4 kPa). For soil, cement and Difa Soil Stabilizer mix, highest UCS value was obtained at 0.6% Difa Soil Stabilizer i.e 720,4 kPa at 14 days of curing with 18.012 % lower than maximum UCS value. Keywords : UCS, Difa Soil Stabilizer, high plasticity, cement, stabilization